Effect of Long-Term Repeated Interval Rehabilitation on the Gross Motor Function Measure in Children with Cerebral Palsy - Stark, Christina; Duran, Ibrahim; Martakis, Kyriakos; Spiess, Karoline; Semler, Oliver; Schoenau, Eckhard (Neuropediatrics, 2020)
Background The efficacy of interventions for cerebral palsy (CP) has been frequently investigated with inconclusive results and motor function measured by the Gross Motor Function Measure (GMFM-66) is common.Objective In this observational analysis, we quantify the GMFM-66 change scores of the second and third year of a multimodal rehabilitation program (interval rehabilitation including home-based, vibration-assisted training) in children with CP.Methods The study was a retrospective analysis of children with CP (2–13 years) participating for a second (n = 262) and third year (n = 86) in the rehabilitation program with GMFM-66 scores at start (M0), after 4 months (M4) of intensive training, and after 8 months of follow-up (M12). A method was previously developed to differentiate between possible treatment effects and expected development under standard of care for GMFM-66 scores using Cohen's d effect size (ES; size of difference).Results After the treatment phase of 4 months (M4) in the second year, 125 of 262 children were responder (ES ≥ 0.2) and 137 children nonresponder (ES < 0.2); mean ES for nonresponder was −0.212 (trivial) and for responder 0.836 (large). After M4 in the third year, 43 children of 86 were responder (ES = 0.881 [large]) and 43 nonresponder (ES = −0.124 [trivial]).Discussion and Conclusion Repeated rehabilitation shows a large additional treatment effect to standard of care in 50% of children which is likely due to the intervention, because in the follow-up period (standard of care), no additional treatment effect was observed and the children followed their expected development.
Keywords: cerebral palsy; gross motor function; GMFM-66; effect size; long-term